Agricultural Land Punching Problems Under The Hands Customically (Cinta Maju Village Study, Samosir Regency) - Imman Yusuf Sitinjak; Ida Nadirah (IHSA Institute, 2022)
This study aims to find out about the customary pawning of agricultural land in the village of Cinta Maju, Samosir Regency.The pawning of land that occurred in the village was a legal act long ago, so land pawning that is tens of years old is still found, with the object of pawning agricultural land and agricultural land. The binding of the land pledge was made on a stamp letter a long time ago and there is a letter affixed with a stamp made by the pawning parties with witnesses being local elders/traditional elders. The legal rules regarding land pawn agreements that occur in the community must follow the rules of customary law. This study analyzes data qualitatively. The method of approach to this research is normative. Source of data used secondary data. Data collection tools used with documentation studies. Location in Samosir Regency, Sitiotio sub-district, Cinta Maju Village. The village's customary rules still demand repayment of new debts to release their lien rights, because of the importance of awareness from the community itself about debts that must be paid, in the law it is termed